2023
DOI: 10.1186/s12951-023-02150-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antidepressant effects of BDNF-quercetin alginate nanogels for depression therapy

Dong Xu,
Li-Na Gao,
Xu-Jiao Song
et al.

Abstract: Background Brain-derived neurotrophic factor (BDNF) with neuronic development and function is a promising therapeutic agent for treating depressive disorder, according to the neurotrophin hypothesis. However, the delivery of BDNF into the brain is not easy as these large protein molecules cannot efficiently cross the blood-brain barrier (BBB) and easily suffer oxidative damage in vivo. Therefore, the quercetin-based alginate nanogels (quercetin nanogels) loaded with BDNF have been developed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Moreover, these materials effectively reversed depressive behavior, reduced anhedonia and weight loss, as well as improved inflammatory cytokine levels and dramatic pyramidal cell damage in the hippocampal CA1 and CA3 subregions of a rat model. Quercetin nanogels also improved CUMS-induced cell apoptosis and proliferation in the hippocampal region (Xu et al, 2023) .…”
Section: Sodium Alginatementioning
confidence: 88%
See 3 more Smart Citations
“…Moreover, these materials effectively reversed depressive behavior, reduced anhedonia and weight loss, as well as improved inflammatory cytokine levels and dramatic pyramidal cell damage in the hippocampal CA1 and CA3 subregions of a rat model. Quercetin nanogels also improved CUMS-induced cell apoptosis and proliferation in the hippocampal region (Xu et al, 2023) .…”
Section: Sodium Alginatementioning
confidence: 88%
“…Increased sodium alginate concentrations reduce (Kalalo et al, 2022) ; drug loading; great promise for the combined (Xu et al, 2023) ; therapy of depressive disorder when quercetin (Szulc Musioł et al, 2023) nanogels were administered intranasally; showed favorable physico-mechanical characteristics and durability.…”
Section: Sodium Alginatementioning
confidence: 99%
See 2 more Smart Citations
“…There is a paucity of data in the literature on the effects of dietary polyphenols on neurotrophic factors in testes. Reports on the influence of functional foods on these factors have mainly focused on brain structure and function [55][56][57][58][59][60][61][62][63].…”
Section: Trk-c and Nt3 Immunoreactionmentioning
confidence: 99%